PENINGKATAN KETERAMPILAN DOMESTIC WORKER INDONESIA MELALUI PELATIHAN MAKEUP FOTO DI GAYATRI BEAUTY ACADEMY SINGAPORE - Nurina Ayuningtyas; Nurul Hidayah; Amalia wahyu Fitriana; Larasati (Prosiding Seminar Nasional Pengabdian Kepada Masyarakat, 2023)
Abstract It is recorded that there are more than 150 thousand PMI in Singapore working in the domestic and homecare sectors. Some domestic workers attend cosmetology school at Gayatri Beauty Academy Singapore to fill their holiday time. The available curriculum does not yet include photo make up which should be taught to support the success of photography which is closely related to pre-wedding photos which have opportunities for the international make up artist job market. The aim of this community service is to improve the skills of domestic workers in doing photo make up independently. The training participants were 20 domestic workers who were students from Gayatri Beauty Academy Singapore. The implementation method is carried out through the process of training preparation, implementation and evaluation. Training evaluation is carried out using tests and questionnaires on participant satisfaction with activities. The results of the training evaluation showed that participants’ understanding ability was very good at 90%, the practical results showed satisfactory results, while participant satisfaction in terms of material showed that 70% were very satisfied, in terms of instructors it showed that 55% of participants were satisfied and in terms of overall training activities it showed 50 % of participants were satisfied. It can be concluded that this community service activity is able to improve domestic workers’ skills in doing photo make up independently. Abstrak Tercatat terdapat lebih dari 150 ribu PMI berada di Singapura bekerja pada sektor domestik dan homecare. Sebagian domestic worker mengikuti sekolah tata rias di Gayatri Beauty Academi Singapura untuk mengisi waktu libur. Kurikulum yang tersedia, belum memasukan make up foto yang seharusnya diajarkan sebagai penunjang keberhasilan fotografi yang erat kaitannya dengan foto prewedding yang memiliki peluang untuk bursa kerja make up artist internasional. Tujuan dari pengabdian kepada masyarakat ini untuk meningkatkan keterampilan domestic worker dalam melakukan make up foto secara mandiri. Peserta pelatihan sebanyak 20 orang domestic worker yang merupakan peserta didik dari Gayatri Beauty Academi Singapura. Metode pelaksanaan dilakukan melalui proses persiapan, implementasi dan evaluasi pelatihan. Evaluasi pelatihan dilakukan dengan tes dan kuisioner kepuasan peserta terhadap kegiatan. Hasil evaluasi pelatihan menunjukan kemampuan pemahaman peserta sangat baik sebesar 90%, hasil praktik menunjukan hasil yang memuaskan, sedangkan kepuasan peserta dari segi materi menunjukan 70% merasa sangat puas, segi instruktur menunjukan 55% peserta merasa puas dan dilihat dari segi keseluruahn kegiatan pelatihan menunjukan 50% peserta merasa puas. Dapat disimpulkan bahwa kegiatan pengabdian kepada masyarakat ini mampu meningkatkan keterampilan domestic worker dalam melakukan make up foto secara mandiri.